Global crisis and its implications on the political transformation in China - Mária Csanádi; Hairong Lai; Ferenc Gyuris (Hungarian Academy of Sciences, Institute of Economics, 2009)
This paper analyzes the impact of global financial and economic crisis on the process of system transformation in China. First, it details the direct impact of global growth on macroeconomic development and its indirect impact on economic transformation. Second, it analyzes the direct impact of global crisis on macroeconomic decline and its indirect impact on the prospects of political transformation. The paper builds on the basic principles and ideas of the Interactive Party-State model to introduce the concept of transformation dynamics. This concept implies the direction and speed of change of the retreating party-state sphere and the emergence of the field outside of it during the process of transformation. Using this concept a statistical survey was carried out on the economic transformation of the Chinese party-state. Results reveal the disparities of the dynamics of transformation in time, in space, and at different levels of aggregation between 1999 and 2004. A dominant type of transformation dynamics is revealed during this period and the shift of dominant type within that period, sensitive to the trend of certain economic indicators. Based on those findings, the paper projects the dominance of another type of transformation dynamics as a result of the consequences of global crisis. It also outlines the possible impact of this dynamics on the premises of political transformation.
Keywords: B52; D85; N10; P2; P3; P41; P52; 330; system transformation; China; economic transformation; political transformation; spatial disparities in system transformation; Finanzkrise; Systemtransformation; Politische Reform; Wirtschaftswachstum; Wirkungsanalyse; Räumliche Verteilung; China